Recent Approaches in Background Modeling for Static Cameras - Bouwmans, Thierry (Handbook on "Background Modeling and Foreground Detection for Video Surveillance", Chapter 1, 2014)
This chapter gives an overview of recent background modeling and foreground detection, and presents resources, datasets and codes publicly available.